2010
DOI: 10.1038/oby.2009.268
|View full text |Cite
|
Sign up to set email alerts
|

Association of the MC4R V103I Polymorphism With Obesity: A Chinese Case–control Study and Meta‐analysis in 55,195 Individuals

Abstract: Recently, large‐scaled studies suggested a negative association of the infrequent allele of the melanocortin‐4 receptor (MC4R) V103I polymorphism with obesity. We conducted a Chinese case–control study, meta‐analysis in East Asians and in all populations, in order to further assess the association between the V103I polymorphism and reduced body weight and to explore whether the association varies among different ethnic groups. We conducted a case–control study to analyze this polymorphism in 2,012 children of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 38 publications
5
42
1
Order By: Relevance
“…We did not find differences in BMI SDS compared to age-, gender- and puberty-matched noncarrier controls, which is in line with studies showing that both variants occur in obese and nonobese subjects [2,39]. Large-scale meta-analyses have confirmed that both variants reduce the risk of obesity by –21 and –50% for V 103 I and I 251 L, respectively [30,33,41,44]. In our sample, carriers of V 103 I and I 251 L had higher (but still normal) values of high-density lipoprotein cholesterol, which supports a reduced risk of negative metabolic effects of obesity.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…We did not find differences in BMI SDS compared to age-, gender- and puberty-matched noncarrier controls, which is in line with studies showing that both variants occur in obese and nonobese subjects [2,39]. Large-scale meta-analyses have confirmed that both variants reduce the risk of obesity by –21 and –50% for V 103 I and I 251 L, respectively [30,33,41,44]. In our sample, carriers of V 103 I and I 251 L had higher (but still normal) values of high-density lipoprotein cholesterol, which supports a reduced risk of negative metabolic effects of obesity.…”
Section: Discussionsupporting
confidence: 71%
“…Nevertheless, for the two most common variants in MC4R, there are meta-analysis studies involving more than 35,000 nonobese controls and almost 20,000 obese patients. The frequency of the V 103 I variant was higher in the nonobese (3.9%) compared to the obese subjects (2.9%), hence conveying a decreased risk for obesity with an odds ratio of 0.79 [29,41]. A similar polygenic association with reduced obesity risk from meta-analyses has been described for I 125 L [33].…”
Section: Discussionmentioning
confidence: 53%
“…In the pre-GWAS era, the MC4R was the first gene showntounambiguouslyharbouracommonvariantwitha small effect size; the original report already included a meta-analysis of all 12 case-control studies that had been published at that time [41]. The association of the minor allele, coding for Ile103, with leanness was confirmed in subsequentlargermeta-analyseswithuptoalmost124,000 probands [1,[42][43][44].Roughly3-6%ofdifferentpopulations are heterozygous for this variant, which according to Germanpopulation-baseddataentailsa0.5-kg/m 2 reductionin meanBMI [41].ThiswouldqualifythisSNPastheonewith thestrongesteffectsizeofallcurrentlyknowncommonvariants including the SNPs in intron 1 of the fat mass and obesity-associatedgene(FTO) [40](foreffectsizesseetable 1).BecauseotherSNPsinthe5'regionoftheMC4Rarein total linkage disequilibrium with the SNP coding for Val103Ile [1,41],thefunctionalroleofthecSNPrequiresfurtherelucidation.Functionalcharacterizationsofthevariant andwild-typereceptorhaverepeatedlyrevealednodifferences [15,22,45]; a single study reported a two-fold decreasedpotencyoftheMC4RantagonisthAGRP(87-132) [46]fortheIle130variantwhichiscompatiblewiththeas-sumptionthatthevariantreceptorentailsanelevatedfunctionoftheMC4R.…”
Section: Monogenic Obesity and Major Gene Effectsmentioning
confidence: 83%
“…The CPOOA subjects were recruited from children and adolescents aged 7-18 y in 5 elementary and middle schools of Haidian District of Beijing, comprising 637 overweight or obese children and adolescents and 456 normal-weight children and adolescents. The ascertainment strategies for the two study groups have been previously described in detail previously (23,24). We used the uniform BMI percentile criteria for the participants, which were determined in a representative Chinese population (25).…”
Section: Subjectsmentioning
confidence: 99%